In “Tone” with dogs: exploring canine musicality - Claudia Pinelli; Anna Scandurra; Cristina Giacoma; Alfredo Di Lucrezia; Biagio D’Aniello (Animal Cognition)
Abstract This study investigates the musical perception skills of dogs through playback experiments. Dogs were trained to distinguish between two different target locations based on a sequence of four ascending or descending notes. A total of 16 dogs of different breeds, age, and sex, but all of them with at least basic training, were recruited for the study. Dogs received training from their respective owners in a suitable environment within their familiar home settings. The training sequence consisted of notes [Do-Mi-Sol#-Do (C7-E7-G7#-C8; Hz frequency: 2093, 2639, 3322, 4186)] digitally generated as pure sinusoidal tones. The training protocol comprised 3 sequential training levels, with each level consisting of 4 sessions with a minimum of 10 trials per session. In the test phase, the sequence was transposed to evaluate whether dogs used relative pitch when identifying the sequences. A correct response by the dog was recorded as 1, while an incorrect response, occurring when the dog chose the opposite zone of the bowl, was marked as 0. Statistical analyses were performed using a binomial test. Among 16 dogs, only two consistently performed above the chance level, demonstrating the ability to recognize relative pitch, even with transposed sequences. This study suggests that dogs may have the ability to attend to relative pitch, a critical aspect of human musicality.